The influence of real estate brokers’ personalities, psychological empowerment, social capital, and knowledge sharing on their innovation performance: The moderating effect of moral hazard - Chang, Hung-Chung; Lee, Chun-Chang; Yeh, Wen-Chih; Chang, Yi-Lun (Frontiers in Psychology, 2022)
This study proposed and examined a conceptual framework on the influence of real estate brokers’ personalities, psychological empowerment, social capital, and knowledge sharing on their innovation performance, and used moral hazard as a moderating variable. We used structural equation modeling (SEM) for data analysis and estimation. The participants were real estate brokers in Kaohsiung City. A total of 1,000 questionnaires was administered to 100 branch offices of real estate companies, 571 of which were later recovered from 80 branch offices. After removing 52 for being invalid, we were left with 519 valid questionnaires, indicating a 51.9% recovery rate. The empirical results suggest that the real estate brokers’ personalities and psychological empowerment positively and significantly influence social capital; personality and psychological empowerment also positively and significantly influence their innovation performance; and social capital significantly influences knowledge sharing, which in turn positively and significantly influences the brokers’ innovation performance. In environments with higher levels of moral hazard, the influence of social capital on the brokers’ knowledge sharing is significantly diminished.